A retrospective study on clinical management involving post-partum diseases in ruminants at selected farms in Klang Valley, Selangor, Malaysia - Nuriza Tukiran. (2019)
The common post-partum diseases among small and large ruminant in selected farms in Klang Valley is being studies together with the clinical management of the post-partum diseases including common clinical signs, the treatment regime and follow up status for each case. In this study, all medical records from January 2013 to December 2017 being retrieved in order to gain information regarding post-partum diseases related to reproductive system in ruminant. Then, data are being documented into Microsoft Excel. Selected and desired data are being evaluated and presented in bar charts or pie charts. The results revealed that the common post-partum diseases are metritis, endometritis, pyometra, vaginal prolapse, uterine prolapse, retained placenta and uterine tear. Furthermore, the treatment regime for each post-partum disease is different. In the conclusion, there are 7 types of post-partum diseases being reported among small and large ruminant within these 5 years time at selected farms in Klang Valley.